Familial hemiplegic migraine due to L263V SCN1A mutation: Discordance for epilepsy between two kindreds from Douro Valley. (October 2014) - Barros, José; Ferreira, Augusto; Brandão, Ana F; Lemos, Carolina; Correia, Fernando; Damásio, Joana; Tuna, Assunção; Sequeiros, Jorge; Coutinho, Paula; Alonso, Isabel; Pereira-Monteiro, José
Background: SCN1A is the most relevant gene in epilepsy. Only seven SCN1A mutations have been identified in 10 familial hemiplegic migraine (FHM) kindreds worldwide. Cases and kindreds: In 2009, we presented a kindred with FHM due to the L263V SCN1A mutation. In the current study, we report a novel FHM3 kindred from the same village. The first family exhibited the co-occurrence of FHM and epilepsy. No case of epilepsy was observed in the new kindred. An L263V mutation was found in all patients, and the haplotype analysis supports a unique mutational event. Comments: Despite its bioelectric activity, the SCN1A L263V mutation most likely requires a combination of several endogenous or environmental induction stimuli to attain an epileptogenic threshold.